PP2A Regulates Phosphorylation-Dependent Isomerization of Cytoplasmic and Mitochondrial-Associated ATR by Pin1 in DNA Damage Responses - Makinwa, Yetunde; Cartwright, Brian M.; Musich, Phillip R.; Li, Zhengke; Biswas, Himadri; Zou, Yue (Frontiers in Cell and Developmental Biology, 2020)
Ataxia telangiectasia and Rad3-related protein (ATR) is a serine/threonine-protein kinase of the PI3K family and is well known for its key role in regulating DNA damage responses in the nucleus. In addition to its nuclear functions, ATR also was found to be a substrate of the prolyl isomerase Pin1 in the cytoplasm where Pin1 isomerizes cis ATR at the Ser428-Pro429 motif, leading to formation of trans ATR. Cis ATR is an antiapoptotic protein at mitochondria upon UV damage. Here we report that Pin1’s activity on cis ATR requires the phosphorylation of the S428 residue of ATR and describe the molecular mechanism by which Pin1-mediated ATR isomerization in the cytoplasm is regulated. We identified protein phosphatase 2A (PP2A) as the phosphatase that dephosphorylates Ser428 following DNA damage. The dephosphorylation led to an increased level of the antiapoptotic cis ATR (ATR-H) in the cytoplasm and, thus, its accumulation at mitochondria via binding with tBid. Inhibition or depletion of PP2A promoted the isomerization by Pin1, resulting in a reduction of cis ATR with an increased level of trans ATR. We conclude that PP2A plays an important role in regulating ATR’s anti-apoptotic activity at mitochondria in response to DNA damage. Our results also imply a potential strategy in enhancing cancer therapies via selective moderation of cis ATR levels.